The FACTORS ANALYSIS OF SCIENCE PROCESS SKILLS TOWARD GUIDED INQUIRY MODEL IN SCIENCE LEARNING - tesya khaira ulva; Rahmah Evita Putri (Universe, 2021)
ABSTRACT The purpose of this study is to analyze factors Science Process Skills (SPS) in the Guided Inquiry model from several different samples. The method of this study is ex post facto. The sample in this study are five reputable articles published in the international journal in Q3. The method of data collection is the documenting The data was analyzed using field collecting Miles and Huberman model. The analysis results in exsternal factors affecting of increased SPS learners in Guided Inquiry models such as educational interests, teacher readiness, the use of teaching media and cultural. It can be oncluded that there are an outside factor influencing the increase in learners’ SPS despite the differences and similarities in sample, variable and research locations such as learning interests, teacher readiness, the use of teaching media and culture.